Peran Customer Service dalam Peningkatan Layanan Nasabah di Bank Syariah Indonesia Kcp.Lombok Praya - Baiq Sulis Eka Zahidah; Okta Ramadhan; Rizki Iqbal Padjuani; Baiq Nadia Nirwana (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The development of the Islamic banking industry in Indonesia shows a significant upward trend, with a market share reaching 7.5% of total national banking assets by 2023. However, the main challenge faced is the low public understanding of the principles and benefits of Islamic banking, particularly in areas with economic potential such as Central Lombok, which has unique socio-cultural characteristics. Service quality, particularly the role of Customer Service (CS), is crucial in increasing customer satisfaction and loyalty. Several previous studies have highlighted the lack of CS competency in handling complaints and educating about Islamic products, but gaps remain regarding the adaptation of CS services to the local context and the digital era. This study aims to identify the role of CS in improving customer service at Bank Syariah Indonesia KCP Lombok Praya using a quantitative approach that examines the relationship between CS competency and customer satisfaction levels. This research is expected to contribute to increasing the effectiveness of Islamic value-based services and digitalization, while addressing previous research gaps related to the influence of cultural contexts and technology. Theoretically, these results enrich the literature on Islamic banking and customer service, and are practically useful for developing service strategies in the Islamic financial sector.